Fatores preditivos do prognóstico desfavorável em pessoas com dor patelofemoral: uma revisão sistemática - Demarchi, Samantha Janaina (2023)
Identifying predictive factors of patellofemoral pain (PFP) prognosis is important for clinical decision making. Although previous systematic reviews have identified some predictive factors of a poor prognosis, they included studies with inadequate designs to answer the research question and, thus, their results should be considered with caution. To identify, from observational prospective cohort studies, baseline characteristics of people with PFP that are predictive of a poor prognosis. Electronic search performed at PubMed/MEDLINE, Cochrane Central Register of Controlled Trials, Embase, SPORTDiscus, SCOPUS, Web of Science and WorldCat databases (up to April 2022). Only observational prospective cohort studies investigating baseline characteristics of people with PFP that were predictive of a poor prognosis were included. The methodological quality of the included studies was assessed using the Quality in Prognosis Studies Tool (QUIPS). This review was developed according to the guide for systematic reviews of studies of prognostic factors and reported following the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocol (PRISMA-P) guidelines. Only one low risk of bias study was included. At one-year follow-up, the presence of a low/middle education level, poor health, the presence of bilateral symptoms and self-reported swollen knee were independently associated with persistent knee symptoms. A paucity of observational prospective cohort studies investigating baseline characteristics of people with PFP that are predictive of a poor prognosis was identified. The results of this review may assist physical therapists in clinical decision making. However, as only one study was included, further observational prospective cohort studies are needed to confirm this result.